Quantitative and Qualitative Benefits of Using BIM in Design and Construction Stages for Railway Development - Jianfeng Liao; Hwan Yong Kim; Min Ho Shin (Buildings)
As railway infrastructure projects become increasingly complex, the potential of Building Information Modeling (BIM) technology to enhance project efficiency and management has garnered significant attention. This paper analyzes the quantitative and qualitative benefits of BIM in the design and construction stages of railway development projects through case studies and compares its effectiveness in these two phases. The results indicate that BIM primarily benefits the design stage by reducing design errors and optimizing processes to save costs and time, averaging cost savings of USD 41,000 and a reduction of 49 days in project duration. In the construction stage, the impact of BIM is even more pronounced, reflected in reduced rework, dynamic resource management, and shortened project timelines, leading to savings of USD 710,795 and a reduction of 89 to 104.5 days in project duration. The 3D modeling and real-time information-sharing capabilities of BIM significantly enhance cross-departmental collaboration efficiency and information transparency, minimizing rework caused by communication issues and greatly optimizing project management and execution. This study shows that BIM can lay the groundwork for construction during the design phase and further improve project management efficiency during the construction phase.